Effects of Fiscal Capacity, Drinking Water Access, and Consumption on Human Development - Wahyuni, Febiati Nur; Fitanto, Bahtiar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2026)
Human Development Index (HDI) disparities across regions remain a critical development issue in East Java, Indonesia, particularly among districts with limited fiscal capacity and uneven access to basic services. This study aims to examine the effects of fiscal factors, access to safe drinking water, and non-food consumption on HDI in 19 districts of East Java during the 2015–2023 period. The research employs a quantitative associative approach using panel data regression analysis. The Fixed Effect Model (FEM) is selected as the most appropriate estimation technique based on the Chow and Hausman tests. The results indicate that Local Own-Source Revenue (LOSR), Special Allocation Funds (SAF), health expenditure, access to safe drinking water, and non-food consumption expenditure have a positive and significant effect on HDI. In contrast, education expenditure shows a positive but statistically insignificant effect, suggesting inefficiencies in budget allocation. Simultaneously, all variables significantly influence HDI, with strong explanatory power. These findings imply that strengthening regional fiscal capacity, improving the effectiveness of public spending, expanding access to basic services, and enhancing household welfare are essential to achieving sustainable and equitable human development.